Availability management : planning and implementing cross-site mirroring on IBM system i5 - Harris, Nick (IBM redbooks., 2007)
In this IBM℗ʼ Redbooks℗ʼ publication, we introduce the concept of cross-site mirroring (XSM) as implemented in IBM OS/400℗ʼ or i5/OS℗ʼ at V5R3M0 and later. XSM describes the replication of data at multiple sites. It involves the use of clustering, cluster resource groups (CRGs), independent auxiliary storage pools (IASPs), and other components. In this updated version, we include the new i5/OS V5R4 functions of Administrative Domain and Source Site Tracking. We also include preview information of the Target Site Tracking function. An additional component of this highly available technology is that XSM keeps two identical copies of an independent disk pool at two sites to provide high availability and disaster recovery. These sites can be geographically close to one another or far apart, depending on the needs of the business. This book is written for IBM technical professionals, Business Partners, and customers who are considering, planning, and implementing a highly available solution on the IBM System i5<U+00CC><U+0081>⁴©<U+0098> platform.